The giant 1960 tsunami in the context of a 6000‐year record of paleotsunamis and coastal evolution in south‐central Chile - Matos‐Llavona, Pedro I.; Ely, Lisa L.; MacInnes, Breanyn; Dura, Tina; Cisternas, Marco A.; Bourgeois, Joanne; Bruce, David; DePaolis, Jessica; Dolcimascolo, Alexander; Horton, Benjamin P.; Melnick, Daniel; Nelson, Alan R.; et al. (Earth Surface Processes and Landforms, 2022)
The tsunami associated with the giant 9.5 Mw 1960 Chile earthquake deposited an extensive sand layer above organic‐rich soils near Queule (39.3°S, 73.2°W), south‐central Chile. Using the 1960 tsunami deposits, together with eye‐witness observations and numerical simulations of tsunami inundation, we tested the tsunami inundation sensitivity of the site to different earthquake slip distributions. Stratigraphically below the 1960 deposit are two additional widespread sand layers interpreted as tsunami deposits with maximum ages of 4960–4520 and 5930–5740 cal BP. This >4500‐year gap of tsunami deposits preserved in the stratigraphic record is inconsistent with written and geological records of large tsunamis in south‐central Chile in 1575, 1837, and possibly 1737. We explain this discrepancy by: (1) poor preservation of tsunami deposits due to reduced accommodation space from relative sea‐level fall during the late Holocene; (2) recently evolved coastal geomorphology that increased sediment availability for tsunami deposit formation in 1960; and/or (3) the possibility that the 1960 tsunami was significantly larger at this particular location than other tsunamis in the past >4500 years. Our research illustrates the complexities of reconstructing a complete stratigraphic record of past tsunamis from a single site for tsunami hazard assessment. The coastal geomorphology near Queule, Chile preserves evidence of the giant Mw 9.51960 Chile earthquake and two buried paleotsunami deposits within the last 6000 years. Using the 1960 tsunami deposits, eye‐witness observations, and numerical simulations of tsunami inundation, we tested the sensitivity of the site to different earthquake slip distributions. We consider the role of coastal geomorphic evolution, sea‐level history, and tsunami magnitude in the preservation of paleotsunami depositional records.

Subduction zone slip variability during the last millennium, south-central Chile - Dura, Tina; Horton, Benjamin P.; Cisternas, Marco; Ely, Lisa L.; Hong, Isabel; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E.; Parnell, Andrew C.; Nikitina, Daria (Quaternary Science Reviews, 2017)
The Arauco Peninsula (37°-38°S) in south-central Chile has been proposed as a possible barrier to the along-strike propagation of megathrust ruptures, separating historical earthquakes to the south (1960 AD 1837, 1737, and 1575) and north (2010 AD, 1835, 1751, 1657, and 1570) of the peninsula. However, the 2010 (Mw 8.8) earthquake propagated into the Arauco Peninsula, re-rupturing part of the megathrust that had ruptured only 50 years earlier during the largest subduction zone earthquake in the instrumental record (Mw 9.5). To better understand long-term slip variability in the Arauco Peninsula region, we analyzed four coastal sedimentary sections from two sites (Tirúa, 38.3°S and Quidico, 38.1°S) located within the overlap of the 2010 and 1960 ruptures to reconstruct a ∼600-year record of coseismic land-level change and tsunami inundation. Stratigraphic, lithologic, and diatom results show variable coseismic land-level change coincident with tsunami inundation of the Tirúa and Quidico marshes that is consistent with regional historical accounts of coseismic subsidence during earthquakes along the Valdivia portion of the subduction zone (1960 AD and 1575) and coseismic uplift during earthquakes along the Maule portion of the subduction zone (2010 AD, 1835, 1751). In addition, we document variable coseismic land-level change associated with three new prehistoric earthquakes and accompanying tsunamis in 1470–1570 AD, 1425–1455, and 270–410. The mixed record of coseismic subsidence and uplift that we document illustrates the variability of down-dip and lateral slip distribution at the overlap of the 2010 and 1960 ruptures, showing that ruptures have repeatedly propagated into, but not through the Arauco Peninsula and suggesting the area has persisted as a long-term impediment to slip through at least seven of the last megathrust earthquakes (∼600 years).
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Subduction zone segmentation; Tsunami Deposits

Coastal evidence for Holocene subduction-zone earthquakes and tsunamis in central Chile - Dura, Tina; Cisternas, Marco; Horton, Benjamin P.; Ely, Lisa L.; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E. (Quaternary Science Reviews, 2015)
The ∼500-year historical record of seismicity along the central Chile coast (30–34°S) is characterized by a series of ∼M 8.0–8.5 earthquakes followed by low tsunamis (<4 m) occurring on the megathrust about every 80 years. One exception is the AD 1730 great earthquake (M 9.0–9.5) and high tsunami (>10 m), but the frequency of such large events is unknown. We extend the seismic history of central Chile through a study of a lowland stratigraphic sequence along the metropolitan coast north of Valparaíso (33°S). At this site, higher relative sea level during the mid Holocene created a tidal marsh and the accommodation space necessary for sediment that preserves earthquake and tsunami evidence. Within this 2600-yr-long sequence, we traced six laterally continuous sand beds probably deposited by high tsunamis. Plant remains that underlie the sand beds were radiocarbon dated to 6200, 5600, 5000, 4400, 3800, and 3700 cal yr BP. Sediment properties and diatom assemblages of the sand beds—for example, anomalous marine planktonic diatoms and upward fining of silt-sized diatom valves—point to a marine sediment source and high-energy deposition. Grain-size analysis shows a strong similarity between inferred tsunami deposits and modern coastal sediment. Upward fining sequences characteristic of suspension deposition are present in five of the six sand beds. Despite the lack of significant lithologic changes between the sedimentary units under- and overlying tsunami deposits, we infer that the increase in freshwater siliceous microfossils in overlying units records coseismic uplift concurrent with the deposition of five of the sand beds. During our mid-Holocene window of evidence preservation, the mean recurrence interval of earthquakes and tsunamis is ∼500 years. Our findings imply that the frequency of historical earthquakes in central Chile is not representative of the greatest earthquakes and tsunamis that the central Chilean subduction zone has produced.
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Tsunami Deposits